The Relationship Between Neutrophil-to-Lymphocyte Ratio (NLR) and Platelet-to-Lymphocyte Ratio (PLR) and the Severity of Dengue Virus Infection Patients - Sirait, Margareth Duma Sari; Permatasari, Ranti; Loesnihari, Ricke (Universitas Padjadjaran, 2025)
Dengue is a viral infectious disease with a wide spectrum of clinical severity, ranging from mild dengue to severe forms with serious complications. Hematologic markers such as the neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) have been studied as prognostic indicators in various infections, including dengue. Method This was an observational analytic cross-sectional study involving 128 dengue patients admitted to H. Adam Malik General Hospital, Medan. Demographic data and laboratory parameters were analyzed using correlation and comparison tests across severity levels. The median values of NLR and PLR were 3.18 and 53.4, respectively. A positive correlation was observed between NLR and dengue severity, while PLR showed a decreasing trend as severity increased. The lowest PLR values were found in patients with DHF grade II and DSS. NLR and PLR have potential as prognostic biomarkers for predicting the severity and complications of dengue virus infection. Further studies with larger populations are needed for validation. Keywords: Biomarker, dengue, severity.